2019
DOI: 10.20472/ss2019.8.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Women Leadership in Higher Education in Saudi Arabia

Abstract: Gender equality is considered as a challenge that human society need to overcome in order for its long term sustainability. This paper looks at the factors that may be barriers to women rise to leadership in Saudi higher education institutions. Education sector is by far the largest employer for Saudi women and is one of the sectors where women should expectedly face minimum barriers to rise to leadership. Saudi government has recently introduced many reforms (under the 2030 vision) which are expected to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…It also appears that different cultural issues might have different impacts on eating and body shape, with internalization of western media and economic values being more closely related to body and eating issues than internalization of western political values. This difference might suggest that many women in Saudi Arabia are less engaged with political changes than they are with economic and media changes, as has been concluded from a qualitative study of women working in Saudi higher education settings [63].…”
Section: Discussionmentioning
confidence: 99%
“…It also appears that different cultural issues might have different impacts on eating and body shape, with internalization of western media and economic values being more closely related to body and eating issues than internalization of western political values. This difference might suggest that many women in Saudi Arabia are less engaged with political changes than they are with economic and media changes, as has been concluded from a qualitative study of women working in Saudi higher education settings [63].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a shift in women's roles in Saudi society from a solely motherhood role to a multirole with higher education, employment status, and socialization [24][25][26][27][28]. A published study found that full-time working mothers' support timing is essential, including acute support, such as establishing a successful latch needed during the first two weeks after delivery and the necessary long-term support to overcome breastfeeding issues [29].…”
Section: Introductionmentioning
confidence: 99%
“…Although higher education institutions have realized the need for career development for employees yet, the picture is unclear how to cope with this situation in a strategic manner (Davies and Davies, 2010;Gaffney, 2005;Keim and Murray, 2008;Luna, 2010;Middlehurst, 2008;Neefe, 2009;Keller, 2018;Alghofaily, 2019). According to the "Society for Human Resource Management," 32 percent of organizations practiced formal succession planning.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…In particular, the shift toward greater support for females in leadership can be related to increasing discontent with economic circumstances and the attitudes and behaviors of people (Jones et al, 2018). Females faced some obstacles to achieve leadership roles due to job segregation, gender discrimination, race, status, and incompetency (Hodges, 2017;Alghofaily, 2019). Although females entered the labor market, it lacks professional engagement in leadership and management positions (Alaqahtani, 2020)…”
Section: Conceptualization Of Succession Planning and Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation